Delusional Themes Across Affective and Non-Affective Psychoses - Picardi, Angelo; Fonzi, Laura; Pallagrosi, Mauro; Gigantesco, Antonella; Biondi, Massimo (Frontiers in Psychiatry, 2018)
The current debate about the diagnostic significance of delusion revolves around two positions. The neurocognitive position conceives delusion as a non-specific, though polymorphic, symptom. The psychopathological position views features of delusion such as content and structure as having meaningful connections with diagnostic entities. This study aims at contributing to this debate by examining the association between delusional themes and diagnosis in a sample of 830 adult psychotic patients. All diagnoses were made by experienced psychiatrists according to DSM-IV or ICD-10 criteria, and in 348 patients were established with the SCID-I. All patients were administered the Brief Psychiatric Rating Scale (BPRS). In each patient, the presence of somatic delusions and delusions of guilt, grandiosity, and persecution was determined by examining the scores on relevant BPRS items. Delusions of guilt were almost pathognomonic for a psychotic depressive condition (psychotic major depression 40%; psychotic bipolar depression 30%; depressed schizoaffective disorder 8%; bipolar and schizoaffective mixed states 6% and 7%, respectively). Only 1% of patients with schizophrenia and no patient with delusional disorder or bipolar or schizoaffective manic state showed such delusions. The difference between unipolar and bipolar depression and the other diagnostic groups was highly significant. Delusions of grandiosity characterized mostly patients with manic symptoms (bipolar mania 20%; bipolar mixed states 19%; manic schizoaffective disorder 10%). They were observed significantly more often in bipolar mania than in schizophrenia (7%). Persecutory delusions were broadly distributed across diagnostic categories. However, they were significantly more frequent among patients with schizophrenia and delusional disorder compared with depressed and manic patients. Somatic delusions were also observed in all diagnostic groups, with no group standing out as distinct from the others in terms of an increased prevalence of somatic delusions. Our findings suggest a middle position in the debate between the neurocognitive and the psychopathological approaches. On the one hand, the widespread observation of persecutory delusions suggests the usefulness of searching for non-specific pathogenic mechanisms. On the other hand, the association between some delusional contents and psychiatric diagnosis suggests that a phenomenological analysis of the delusional experience may be a helpful tool for the clinician in the diagnostic process.